Aplicación web para la gestión de eventos deportivos de la empresa Otavalo Trail - Zaldumbide Paredes, Ricardo Sebastian (2024)
This research addresses the development of a web application for managing sports events for the company Otavalo Trail, located in the city of Otavalo, Ecuador. The research problem arises due to the rapid growth in the volume of participants in the events organized by the company, which has generated significant operational challenges, such as manual management of registrations, payment verification, and communication with participants. The general objective is to develop a web application that allows Otavalo Trail to manage its sports events more efficiently, reducing operational burden, minimizing errors, and enhancing its growth capacity. The methodology is based on a qualitative approach, using techniques such as observation and unstructured interviews. The Extreme Programming (XP) methodology was adopted for the development of the web application. The results demonstrate that the developed web application addresses Otavalo Trail's operational deficiencies, optimizing key processes such as participant registration, payment processing through secure gateways, and administrative management of events, sponsors, and reports. In conclusion, the development of the web application has proven to be an effective solution to optimize processes, improve user and organizer experience, and lay the foundation for the company's sustainable growth.